The menstrual cycle effect on the force quality (Explosive force) in soccer players: Field study of a team case of Girls Harmony Constantine - SALEH, Halim; MHIMDAT, Rachid (Journal of Human Sciences, 2020)
Soccer has been one of the sports that has attracted attention since its inception and has grown over the years to become the most popular and most pratical sport around the word. The exercise was not limited to men,bu women have a wide range of soccer opportunities through various local and international competitions. However, the biology of women is differnt from the biology of men, which makes the exercise of the sport a study and survey. Due to the effects of this course and its biological source, it is first to study its effects on various aspects of sports préparation, in particular physical preparation through the physical effects of the menstrual cycle. It is in this sense that the idea of this research in which weare examining the menstrual cycle effect on the force quality (Explosive force) in soccer players, Field study of a team case: Girls Harmony Constantine.